DSC and microstructure analysis of high temperature Ni-Ti-Hf, low hysteresis Ni-Ti-Cu and conventional super-elastic and shape memory Ni-Ti alloy ingots and wires. (December 2019) - Lemke, J.N.; Coda, A.
Graphical abstract: Highlights: DSC behavior of Ni-Ti based alloys in various conditions show individual trends. Sample chemistry, microstructure, geometry, surface and processing are considered. Ni-Ti-Cu sensitivity to DSC rate depends on transformation B2↔B19(↔B19') sequence. Large grain size distribution in Ni-Ti-Hf leads to high DSC rate deviations. Low heat capacity of R-phase in binary Ni-Ti supports high DSC rate stability. Abstract: The progression of martensitic transformations in calorimetric experiments on NiTi-based shape memory alloys (SMA) depends significantly on the material composition, processing history and the thermo-mechanical treatment which is performed to prepare the material for use in application. The phase transformations in Ni-Ti alloys are first order transitions, i.e. the microstructure symmetry changes occur spontaneously and superheating and supercooling effects emerge. Thus, the thermal scanning rate in differential scanning calorimetry (DSC) affects the observation of important material parameters for the characterization of shape memory alloys like onset temperatures, hysteresis width and change in enthalpy of phase transformations. This work depicts how the transformation characteristics as observed by DSC measurements vary significantly by altering the alloy composition and processing conditions of the material. An in-depth calorimetric study on a wide range of NiTi-based alloys which were prepared as heat treated ingot and processed wire was performed. In order to evaluate also the rate effect on the transformation of distinct alloys, DSC rates from 1 to 30 °C/min were tested, highlighting the interplay between thermal scanning velocity and material parameters. Manifold results are presented on how chemistry, microstructure, DSC sample geometry and processing stresses in the materials contribute to award the alloys diverging sensitivity to the thermal scanning rate. Deviations in binary Ni-Ti composition alter the sensitivity to heating and cooling rate, e.g. martensitic transformation in annealed super-elastic (SE) wire is stronger affected by the rate than shape memory wire due to differences in the precipitation behavior. Ni-Ti-Hf high temperature shape memory alloys show a rather small enlargement of hysteresis, but a huge shift in transformation temperatures, while Cu addition to Ni-Ti causes very sensitive hysteresis changes up on modifying thermal rates which is assigned to B19 orthorhombic transformation. Transformation parameters of wires are less affected by DSC rates than ingots due to their high surface to volume ratio, while sample weight and surface finish is observed to have a minor impact. Small grains and residual strains owing to processing history of drawn wire tend to stabilize the transformation. In materials which exhibit R-phase transformation, the low heat capacity of this phase could be responsible for its minor sensitivity to variations in DSC rate.